Biomarker concentrations in white and British Indian vegetarians and non-vegetarians in the UK Biobank - Perez-Cornago, A; Bradbury, K; Key, T (Oxford University Press, 2021)
Background: Prospective studies have shown differences in some disease risks between vegetarians and non-vegetarians, but the potential biological pathways are not well understood.